Biofortified crops for tackling micronutrient deficiencies – what impact are these having in developing countries and could they be of relevance within Europe?. Issue 4 (8th November 2018) - Lockyer, S.; White, A.; Buttriss, J. L.
Abstract: The development of crops that by harvest have accumulated higher amounts of a particular micronutrient than standard crops is known as biofortification. Biofortified staple crops such as provitamin A‐biofortified sweet potato ('orange sweet potato'), zinc‐biofortified rice ('zinc rice') and iron‐biofortified beans ('iron beans'), developed by selective breeding, have been introduced into developing countries with the goal of reducing micronutrient deficiencies. In these settings, micronutrient deficiencies caused by low dietary intakes and exacerbated by inflammation and infection result in considerable morbidity and mortality worldwide. The aim of this review is twofold: (1) to describe the impact of biofortified crops on micronutrient intake, nutritional status and other biological endpoints in developing countries and (2) to consider the relevance of these nutritional effects in other parts of the world such as Europe. Regular consumption of biofortified crops in developing countries where micronutrient deficiency is common has been shown to increase micronutrient intakes and thus help meet the World Health Organization's dietary recommendations. In terms of micronutrient status, most research has been conducted using provitamin A‐biofortified crops (particularly orange sweet potato), with large 2‐ to 3‐year studies indicating increases in plasma retinol, though additional studies measuring change in body stores would provide more definitive evidence. There is some evidence to suggest that iron‐biofortified crops can increase iron status (measured by serum ferritin and total body iron), but further studies are required to demonstrate the efficacy of zinc‐biofortified foods. Intakes of some micronutrients are low in some UK population subgroups (in particular adolescents and young adult women), with sizeable proportions having intakes below the lower reference nutrient intake. There is also evidence of low status for some nutrients ( e.g . iron and in particular vitamin D), although the prevalence of iron deficiency is much less, and therefore the consequences less severe, than seen in the developing world. The final part of the paper describes strategies used to improve micronutrient intake in Europe, such as fortification of bread flour post‐harvest and supplementation with vitamin D and folic acid, and discusses whether there is a role for biofortified crops in the UK.